Problem-based learning environments in Moodle: Implementation approches - Ali, Zeyad F.; Al-Dous, Khulood; Samaka, Mohammed (IEEE Global Engineering Education Conference, 2015)
Problem-based learning (PBL) educators resorted to developing their own environments even with existence of comprehensive Learning Management Systems (LMS). They realized that both commercial and open source systems were designed with traditional lecture-based instruction in mind. The systems lack the features and scenarios required by the inherently collaborative, dynamic, and timely pedagogy. The presence of several PBL flavors and models added more complexity to the development process preventing any single environment from being unanimously recognized by the PBL community. In this paper, we review and discuss the implementation approaches that were used in developing PBL environments in the open-source LMS Moodle. We focus on the instantiation methodologies, scaffolding, customizability, features, and flexibility. We go over a wide range of PBL implementations starting from the basic ones that used whatever features available without adding any new functionality. We then browse two Moodle environments that implemented a particular PBL model. Finally, we discuss a two environment that used scripting in two different forms, one benefitted from a standard like IMS Learning Design (IMS-LD) and the other made use of a specially developed PBL Domain-Specific Modelling Language (DSML).